Enlightening the People Educating the Nation: The Contribution of K.H. Hussein Muhammad's Thought in Islamic Education - Nur Halizsah Andini; Aldi Wijaya Dalimunthe (Spiritus: Religious Studies and Education Journal, 2025)
Islamic education has a strategic role in building a just and dignified national character. This article examines the thoughts of K.H. Husein Muhammad, a scholar who integrates Islamic values with a modern approach, which emphasizes the importance of inclusiveness, justice, and women's empowerment in education. This research uses a descriptive qualitative approach with a literature study of his book entitled Islam that Enlightens and Educates. The results showed that K.H. Husein Muhammad's thoughts on Islamic education are relevant to creating a generation with strong character, critical, and able to adapt to global challenges. According to him, enlightened and intellectualizing Islamic education must be able to build people's awareness and form individuals who are not only intellectually intelligent but also moral.